Guia para la documentacion de recursos geneticos: Un enfoque autodidactico para la comprension, análisis y desarrollo de la documentacion de los recursos geneticos - Painting, Kevin A.; Perry, M.C.; Denning, R.A.; Ayad, W.G.; International Plant Genetic Resources Institute (1993)
This Guidebook comes with Genebank Management System Software User's Guide, a tutorial and reference guide for use with the Genebank Management System Software (GMS). This guidebook will assist users in making their own decision on the analysis, design, implementation and use of both manual and microcomputer-based documentation systems. (Chinese and French versions available)